2021
DOI: 10.7554/elife.70307
|View full text |Cite
|
Sign up to set email alerts
|

Structural heterogeneity of cellular K5/K14 filaments as revealed by cryo-electron microscopy

Abstract: Keratin intermediate filaments are an essential and major component of the cytoskeleton in epithelial cells. They form a stable yet dynamic filamentous network extending from the nucleus to the cell periphery, which provides resistance to mechanical stresses. Mutations in keratin genes are related to a variety of epithelial tissue diseases. Despite their importance, the molecular structure of keratin filaments remains largely unknown. In this study, we analyzed the structure of keratin 5/keratin 14 filaments w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 98 publications
4
24
0
Order By: Relevance
“…The intermediate filaments we found have less density in their core, supporting the idea that they are tubular ( Parry and Steinert, 1999 ; Watts et al, 2002 ). During the revision of this paper, two cryo-ET studies reported that the nonneuronal intermediate filaments vimentin and keratin are also tubular ( Eibauer et al, 2021 Preprint ; Weber et al, 2021 ). This architecture is therefore likely a common feature of these filaments.…”
Section: Discussionmentioning
confidence: 99%
“…The intermediate filaments we found have less density in their core, supporting the idea that they are tubular ( Parry and Steinert, 1999 ; Watts et al, 2002 ). During the revision of this paper, two cryo-ET studies reported that the nonneuronal intermediate filaments vimentin and keratin are also tubular ( Eibauer et al, 2021 Preprint ; Weber et al, 2021 ). This architecture is therefore likely a common feature of these filaments.…”
Section: Discussionmentioning
confidence: 99%
“…Here also, their heterogeneity is a major obstacle. In a recent cryoEM study [ 61 ], in vivo assembled keratin networks were shown to feature significant diameter fluctuations even along a single filament. Moreover, the 10 nm cytoplasmic filaments appeared quite smooth and lack specific surface features.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…At the same time, the filaments isolated from living cells are obviously presenting a very attractive study object. However, heterogeneity was also observed for such filaments [ 61 ]. Several post-translation modifications are known to affect the assembly process of IF proteins [ 22 ].…”
Section: Use Of Chemical Cross-linking To Reveal the 3d Architecture Of Complete Filamentsmentioning
confidence: 99%
“…This was possible because each extracted particle was saved with its original coordinates. The filaments are reconstituted in silico [ 11 , 35 ]. To properly analyze reconstituted filaments, we also applied an unbending algorithm from ImageJ [ 36 ].…”
Section: Methodsmentioning
confidence: 99%